Organización contable en el Comercial Castillo del Sr. Castillo Toro Simón de Jesús, de la ciudad de Zamora, período del 01 de abril al 30 de junio 2023. - Apolo Buele, María Magdalena (2024)
The Work of Curricular Integration called Accounting Organization in the Commercial Castle of Mr. Castillo Toro Simón de Jesús, from the city of Zamora, from April 1 to June 30, 2023, was developed with the purpose of performing an accounting process according to the needs of the business, in order to know the economic situation-financial statements, contributing to sound resource management and sound decision-making. In order to meet the objectives set, it began with the preparation of an accounting plan that was adjusted to the economic activity of the company, in which it systematically details all the accounts which were necessary for the recording of accounting events generated in the economic period, then the respective manual of accounts was made in which the concept of each accounting account was described by disclosing its debits, credits and the corresponding balance; supplementary books were developed which simplified the operations at the time of their registration in the journal such as: purchasing assistant, sales assistant, accounts receivable and accounts payable. Subsequently, the accounting process was carried out, starting with the initial inventory, which was carried out through the physical verification of goods, rights and obligations of the company, thus allowing the Initial Situation Statement to be drawn up, the same that reflected a total of Assets of $120,063.58, Liabilities with a value of $1,789.71 and an Equity of $118,273.87. Then the transactions were recorded in the Journal, then the balance of the accounts in the General Ledger was moved to structure the Checking Balance, the Worksheet and finally the presentation of the Financial Statements with their respective explanatory notes. It is worth mentioning that the multiple account system was used to control the goods account. The methodology of the work has a mixed approach of exploratory-descriptive type using the corresponding methods and techniques. The results of the accounting process allowed to know through the Statement of Financial Position an Asset of $ 118,885.28, Liabilities of $ 4,042.26 and an Equity of $ 114,843.03; on the other hand, the Statement of Results reveals a total income of $ 2,204,45 and total expenses of $5,635.29 resulting in a loss of $3,430.84 in the current year. Finally, the conclusions and recommendations are presented, hoping that the owner will continue with the proposal of the developed accounting organization that will allow him to obtain reliable financial statements for the development and growth of the company.